Controlling the Revolving and Rotating Motion Direction of Asymmetric Hexameric Nanomotor by Arginine Finger and Channel Chirality - Guo, Peixuan (ACS Nano, 2019)
[Image: see text] Nanomotors in nanotechnology are as important as engines in daily life. Many ATPases are nanoscale biomotors classified into three categories based on the motion mechanisms in transporting substrates: linear, rotating, and the recently discovered revolving motion. Most biomotors adopt a multisubunit ring-shaped structure that hydrolyzes ATP to generate force. How these biomotors control the motion direction and regulate the sequential action of their multiple subunits is intriguing. Many ATPases are hexameric with each monomer containing a conserved arginine finger. This review focuses on recent findings on how the arginine finger controls motion direction and coordinates adjacent subunit interactions in both revolving and rotating biomotors. Mechanisms of intersubunit interactions and sequential movements of individual subunits are evidenced by the asymmetrical appearance of one dimer and four monomers in high-resolution structural complexes. The arginine finger is situated at the interface of two subunits and extends into the ATP binding pocket of the downstream subunit. An arginine finger mutation results in deficiency in ATP binding/hydrolysis, substrate binding, and transport, highlighting the importance of the arginine finger in regulating energy transduction and motor function. Additionally, the roles of channel chirality and channel size are discussed as related to controlling one-way trafficking and differentiating the revolving and rotating mechanisms. Finally, the review concludes by discussing the conformational changes and entropy conversion triggered by ATP binding/hydrolysis, offering a view different from the traditional concept of ATP-mediated mechanochemical energy coupling. The elucidation of the motion mechanism and direction control in ATPases could facilitate nanomotor fabrication in nanotechnology.